Estratégia tecnológica e desempenho inovador: análise das pequenas e médias empresas produtoras de equipamentos médico-hospitalares de São Carlos e Ribeirão Preto. - Rieg, Denise Luciana (2004)
The goal of this thesis is to identify innovation performances and technology strategies (TSs) adopted by medical equipment firms (those that are technology-based firms (TBFs) or not), located in São Carlos and Ribeirão Preto. Two hypotheses were delineated: (1) the medical equipment firms located in São Carlos and Ribeirão Preto that reached higher innovation performances in the last three years, differ from the ones that reached lower innovation performances in the dimensions of their technology strategies; and (2) the medical equipment technology-based firms located in São Carlos and Ribeirão Preto differ from the ones which are not considered as technology-based firms in the dimensions of their technology strategies. In order to analyze those hypotheses, data about TBF status, TS, and innovation performance were collected from thirty nine medical equipment producers located in São Carlos and Ribeirão Preto. An structured questionnaire was utilized for this purpose. The analysis of this information shows that the technology strategies adopted by the medical equipment firms that reached higher innovation performances are different in many aspects from the ones adopted by those that reached lower innovation performances. There are also differences between the TSs adopted by the medical equipment technology-based firms and the TSs adopted by those which are not considered as technology-based firms. Regarding the firms which reached higher and lower innovation, some indications were obtained that larger investments in internal activities of research and development and in external sources of technology, larger dedication to technology forecasting, and development of a wide portfolio of product and process technologies have allowed the firms to reach larger innovation performances. Regarding TBFs and Not-TBFs, it was observed that the TBFs have worked for the enlargement of their innovation and acquisition capacities of product technologies. Examples of their efforts: (1) large investments in internal R&D activities destined to innovations in product; (2) the number of engineers and scientists allocated to these activities; (3) the amount of key product technologies that those firms have; and (4) their large dedication to technology forecasting, etc. On the other hand, there were indications that N-TBFs (when they carry out some technological effort) dedicate themselves to the enlargement of their operation and adaptation capacities to operate their facilities more efficiently.